Cybercrime behaviour in the context of youth development - Jaya, M. Izham; Ab Razak, Mohd Faizal; Mohamad, Mastura; Hisham, Syifak Izhar (Philstat.org.ph, 2022)
The positive growth of youth is vital in the development of the particular country. Thus, it is crucial to acknowledge the factors that contribute to positive youth development. Using a bibliometric analysis approach, this study investigated the research contribution in the fields of positive youth development by finding the information related to the annual growth of publication, research areas, top 20 impactful journals, and highly cited articles and authors. This study aimed to present an extensive knowledge map of Malaysian youth development by accumulating a 10-year dataset from the Scopus database. Articles published between 2011 until 2021 were analysed using bibliometric approach. Searching the keyword “youth”, 3354 articles were found. After refining with the keywords of “Malaysia Youth”, 528 articles were then collected. In addition, this paper collected data from the Institute for Youth Research Malaysia, a leading centre in researching youth and their development in Malaysia. It is proven that health (stress-free, worry-free), social relations (relationship with parents), and safety (security while using the internet) had a significant relationship in cybercrime behaviour among Malaysian youth. Furthermore, this study discussed the contributions and significance of youth studies in the latest research studies together with the future direction.